Rapid Detection and Quantification of Plant Innate Immunity Response Using Raman Spectroscopy - Chung, Pil Joong; Singh, Gajendra P.; Huang, Chung-Hao; Koyyappurath, Sayuj; Seo, Jun Sung; Mao, Hui-Zhu; Diloknawarit, Piyarut; Ram, Rajeev J.; Sarojam, Rajani; Chua, Nam-Hai (Frontiers in Plant Science, 2021)
We have developed a rapid Raman spectroscopy-based method to detect and quantify early innate immunity responses in Arabidopsis and Choy Sum plants. Arabidopsis plants challenged with flg22 and elf18 elicitors, could be differentiated from mock- treated plants by their Raman spectral fingerprints. From the difference Raman spectrum and the p-value at each Raman shift we derived the Elicitor Response Index (ERI) as a quantitative measure of the response whereby a higher ERI value indicates a more significant elicitor-induced immune response. Among the various Raman spectral bands contributing towards the ERI value, the most significant changes were observed in those associated with carotenoids and proteins. To validate these results, we investigated several characterized Arabidopsis pattern-triggered immunity (PTI) mutants. Compared to wild type (WT), positive regulatory mutants had ERI values close to zero whereas negative regulatory mutants at early time points had higher ERI values. Similar to elicitor treatments, we derived an analogous Infection Response Index (IRI) as a quantitative measure to detect early PTI response in Arabidopsis and Choy Sum plants infected with bacterial pathogens. The Raman spectral bands contributing towards the high IRI value were largely identical to the ERI Raman spectral bands. Raman spectroscopy is a convenient tool for rapid screening for Arabidopsis PTI-mutants and may be suitable for non-invasive and early diagnosis of pathogen-infected crop plants